Sarbanes-Oxley IT compliance using COBIT and open source tools - Lahti, Christian; Peterson, Roderick (Rockland, MA : Syngress Pub., 2005)
This book illustrates the many Open Source cost savings opportunities available to companies seeking Sarbanes-Oxley compliance. It also provides examples of the Open Source infrastructure components that can and should be made compliant. In addition, the book clearly documents which Open Source tools you should consider using in the journey towards compliance. Although many books and reference material have been authored on the financial and business side of Sox compliance, very little material is available that directly address the information technology considerations, even less so on how Open Source fits into that discussion. Each chapter begins with an analysis of the business and technical ramifications of Sarbanes-Oxley as regards to topics covered before moving into the detailed instructions on the use of the various Open Source applications and tools relating to the compliance objectives. The bootable CD contains fully configured demonstrations of Open Source tools. * Shows companies how to use Open Source tools to achieve SOX compliance, which dramatically lowers the cost of using proprietary, commercial applications * Contains a bootable-Linux CD containing countless applications, forms, and checklists to assist companies in achieving SOX compliance * Only SOX compliance book specifically detailing steps to achieve SOX compliance for IT Professionals.
Introduction The Goals of this Book -- Chapter 1: Sox and Cobit Defined -- Chapter 2: Cost of Compliance -- Chapter 3: Why Open Source -- Chapter 4: Domain 1 -- Planning and Organization Chapter 5: Domain 2 -- Acquisition and Implementation Chapter 6: Domain 3 -- Delivery and Support -- Chapter 7: Domain 4 -- Monitoring -- Chapter 8: The Bottom Line -- Appendix -- CD Contents At a Glance.
Includes index.
Keywords: Information technology -- Management; United States; Sarbanes-Oxley Act of 2002 (United States); Electronic books